The concept of ‘smart cities’. Towards community development? - Anastasia Stratigea (Netcom)
The value of ICTs in support of a variety of functions in urban environments, serving people, businesses and governmental institutions is nowadays greatly acknowledged. The concept of ‘smart’ cities has emerged, where local innovation systems, largely supported by digital networks and their applications, are contributing to the: diffusion of knowledge and information, knowledgeable decision making, network cooperation, efficient interaction among various actors and intelligence gathering. The aim of the paper is to indulge in the concept of ‘smart’ cities for inclusive community development. The first part elaborates on the concept of ‘smart’ city, by exploring its various meanings, key dimensions, and potential for community development. In the second part, the Greek experience is presented, by means of a prominent example of a Greek ‘smart’ city, developing city-specific ICTs applications for inclusive community development. Finally, in the last part, some conclusions and future prospects of the concept of ‘smart’ cities for community development in Greece are drawn.